Psychological flexibility of female students of kindergarten department (Journal of the College of Basic Education, 2022)
The current research aims to identify the psychological resilience of female students in the kindergarten department. The current research determined the female students of the kindergarten department at (Al-Mustansiriya University / College of Basic Education) for the academic year 2020-2021, morning and evening studies, and the researcher built the psychological resilience scale, as the number of its final paragraphs reached (26) paragraphs, and their psychometric properties were verified and applied The two tools were based on a sample of (339) female students, randomly selected from the kindergarten department in (College of Basic Education - Al-Mustansiriya University), for the academic year (2020-2021).